2006
DOI: 10.1557/proc-0937-m03-19
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Polythiophene Films Produced via Surface Polymerization by Ion-Assisted Deposition: A Combined Experimental and Computational Study

Abstract: Control of film morphology is widely recognized as one of the limiting factors in the development of conjugated polymers for photonic and electronic applications. Surface polymerization by ion-assisted deposition (SPIAD) is shown to drive film morphology. A wide variety of structures form in the SPIAD polythiophene films, including islands, lamellar structures, nanoscale crystallites, and fractal-like growth patterns. Density functional theory-molecular dynamic simulations are utilized to illustrate the manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Enhanced bonding in ion-assisted deposition of oligothiophenes has been observed previously [11][12][13] and was predicted by molecular dynamic simulations. 14 Ongoing work is exploring a similar mechanism in which the 4T þ PbS þ ion films display enhanced covalent bonding between the PbS nanoparticles and the 4T phase, induced by ion-assisted modification.…”
Section: B Xps Analysis Of Core Level Shifts Due To Green Laser Illusupporting
confidence: 70%
See 1 more Smart Citation
“…Enhanced bonding in ion-assisted deposition of oligothiophenes has been observed previously [11][12][13] and was predicted by molecular dynamic simulations. 14 Ongoing work is exploring a similar mechanism in which the 4T þ PbS þ ion films display enhanced covalent bonding between the PbS nanoparticles and the 4T phase, induced by ion-assisted modification.…”
Section: B Xps Analysis Of Core Level Shifts Due To Green Laser Illusupporting
confidence: 70%
“…10 The acetylene ions used in ion-assisted deposition behave both as catalysts and reagents by energetically inducing bonding between condensed phase species and forming adducts with the neutral reagents. [11][12][13][14][15] X-ray photoelectron spectroscopy (XPS) was employed to probe photoconductivity of the PbS nanoparticle-4T composite films. For insulating and semiconducting samples, it has been observed that surface charging can shift the measured binding energies in an X-ray photoelectron (XP) spectrum.…”
Section: Introductionmentioning
confidence: 99%